Fisheries oceanography and the ecology of early life histories of fishes: a perspective over fifty years - Govoni, John Jeffrey (Scientia Marina, 2005)
Fisheries oceanography can be defined as the study of the ecology of fishes in the ocean: so defined, it comprises study at all levels of ecological organization—organisms, populations, communities, and ecosystems. The early life history of fishes plays out at each of these levels of organization. A paradigm developed by Johan Hjort at the turn of the twentieth century, along with postulates by Hjort and many of his colleagues that followed, came to guide much of fisheries oceanography through the ensuing hundred years. Research themes that address these postulates can be roughly partitioned as the study of the physiological ecology of the eggs and larvae of fishes in the sea, and the study of the abundance and distribution of fish propagules. Using case studies of organisms and physical processes, considerable progress has been made in understanding the causes of variation in population recruitment, defined either by stage-based models and simulated by individual-based models. Some of this progress has been published in Scientia Marina, or its predecessor Investigación Pesquera. The causes of variation, however, are interactive and operative at differing, yet often overlapping, spatial and temporal scales. Difficulty in matching spatial scales that typically differ by an order of magnitude or more, will continue to trouble the resolution of causes of population recruitment. Moreover, study of the causes of variation in recruitment has not led to predictive power at an annual scale. Prediction at a decadal scale, using community (or more appropriately larval fish assemblages) and ecosystem level dynamics, is more hopeful.